Does first‐line treatment have prognostic impact for unresectable HCC?—Atezolizumab plus bevacizumab versus lenvatinib. (3rd June 2022) - Hiraoka, Atsushi; Kumada, Takashi; Tada, Toshifumi; Hirooka, Masashi; Kariyama, Kazuya; Tani, Joji; Atsukawa, Masanori; Takaguchi, Koichi; Itobayashi, Ei; Fukunishi, Shinya; Tsuji, Kunihiko; Ishikawa, Toru; et al.
Abstract: Background/Aim: A comparison of therapeutic efficacy between atezolizumab plus bevacizumab (Atez/Bev) and lenvatinib treatment given as first‐line therapy for unresectable hepatocellular carcinoma (u‐HCC) in regard to progression‐free survival (PFS) overall survival (OS) has not been reported. We aimed to elucidate which of those given as initial treatment for u‐HCC has greater prognostic impact on PFS and OS of affected patients, retrospectively. Materials/Methods: From 2020 to January 2022, 251 u‐HCC (Child–Pugh A, ECOG PS 0/1, BCLC‐B/C) treated were enrolled (Atez/Bev‐group, n  = 194; lenvatinib‐group, n  = 57). PFS and OS were analyzed following adjustment based on inverse probability weighting (IPW). Results: There was a greater number of patients with macro‐vascular invasion in Atez/Bev‐group (22.7% vs. 8.8%, p  = 0.022). In lenvatinib‐group, the frequencies of appetite loss (38.6% vs. 19.6%, p  = 0.002), hypothyroidism (21.1% vs. 6.7%, p  = 0.004), hand foot skin reaction (19.3% vs. 1.0%, p  < 0.001), and diarrhea (10.5% vs. 4.6%, p  = 0.012) were greater, while that of general fatigue was lower (22.8% vs. 26.3%, p  = 0.008). Comparisons of therapeutic best response using modified response evaluation criteria in solid tumors (mRECIST) did not show significant differences between the present groups (Atez/Bev vs. lenvatinib: CR/PR/SD/PD = 6.1%/39.1%/39.1%/15.6% vs. 0%/48.0%/38.0%/14.0%, p  = 0.285). In patients of discontinuation of treatments, 48.2% switched to lenvatinib, 10.6% continued beyond PD, 8.2% received another systemic treatment, 5.9% underwent transcatheter arterial chemoembolization (TACE), 3.5% received hepatic arterial infusion chemotherapy (HAIC), and 1.2% underwent surgical resection in Atez/Bev‐group, while 42.2% switched to Atez/Bev, 4.4% continued beyond PD, 4.4% received another systemic treatment, 2.2% nivolumab, 6.7% received TACE, and 2.2% received HAIC in lenvatinib‐group. Following adjustment with inverse probability weighting (IPW), Atez/Bev‐group showed better PFS (0.5−/1−/1.5‐years: 56.6%/31.6%/non‐estimable vs. 48.6%/20.4%/11.2%, p  < 0.0001) and OS rates (0.5−/1−/1.5‐years: 89.6%/67.2%/58.1% vs. 77.8%/66.2%/52.7%, p  = 0.002). Conclusion: The present study showed that u‐HCC patients who received Atez/Bev as a first‐line treatment may have a better prognosis than those who received lenvatinib. Abstract : This is a first report mentions that a comparison of therapeutic efficacy between atezolizumab plus bevacizumab (Atez/Bev) and lenvatinib treatment given as first‐line therapy for unresectable hepatocellular carcinoma (u‐HCC) in regard to overall survival (OS). Although tumor responses did not show significant differences between both groups, Atez/Bev‐group showed better OS rates following adjustment with IPW (0.5−/1−/1.5‐years: 89.6%/67.2%/58.1% vs. 77.8%/66.2%/52.7%, p  = 0.002). Atez/Bev‐group showed better OS as a first‐line treatment as compared to lenvatinib‐group.